Investigating the effect of graphene on eutectic salt properties for thermal energy storage. (November 2019) - Ahmed, Sumair Faisal; Khalid, Mohammad; Walvekar, Rashmi; Vaka, Mahesh; Mubarak, Nabisab Mujawar; Chamkha, Ali; Khalid, Muhammad
Graphical abstract: Highlights: Low temperature molten salt was synthesized for thermal energy storage. Graphene doped low temperature molten salt shows enhancement in heat capacity and thermal conductivity. No Alteration in thermal stability before and after doping graphene in molten salt. Good prediction of heat capacity and thermal conductivity by various models except Nan's model. Abstract: Enhancement of heat capacity and thermal conductivity with the dispersion of graphene nanoparticles into low-temperature eutectic salt was investigated. Three different nanoparticle concentrations (0.01, 0.05 & 0.1 wt. %) were dispersed into a eutectic salt mixture composed of 5.66% NaNO3, 21.25% KNO3, 24.75% Ca(NO3 )2, 41% CsNO3, & 7.34% LiNO3 by weight. The results show that the graphene doping resulted in enhanced heat capacity ranging from 5 to 13%, whereas thermal conductivity increased marginally by ˜3%, with respect to graphene concentration. Various theoretical models were tested to predict the thermal conductivity and heat capacity of the graphene-doped eutectic salt. The Maxwell and Hamilton-Crosser thermal conductivity models showed good agreement with experimental results, with a deviation of ±3%, while Nan's thermal conductivity model over-predicted the thermal conductivity value. The conventional heat capacity equation fits well with the experimental data, with deviation <14%.